MENIMBANG DEMOKRASI DELIBERATIF DALAM PROSES PEMBENTUKAN HUKUM YANG DEMOKRATIS DI INDONESIA - Sukma, Fadjar; Saparuli (IBLAM LAW REVIEW, 2021)
Citizens as subjects as well as objects of law have an important role in the process of forming laws that apply as a model that becomes patterns of interaction in the life of the state and society as well as an order of behavior that must be fulfilled. This is also in line with the latent spirit of the Indonesian nation, namely "consensus" in making a decision or policy. But now democracy in Indonesia is only defined as the election of the president and vice president and representative institutions to sit in parliament. After that, public participation in various aspects of life seemed to be abolished, especially in terms of the formation of a regulation or law which actually directly affects people's lives, even though our constitution mandates that the highest power is in the hands of the people. A study on liberalized democracy popularized by Jurgen Hambermas emphasizes the active participation of the community as a pillar in direct supervision and inspection as well as on the formation of laws outside the parliament in order to direct the quality of Indonesian law towards a better direction.